Oncological outcomes of surgery for isolated retroperitoneal recurrence in renal cancer patients after radical nephrectomy - Staník, Michal; Poprach, Alexander; Littnerová, Simona; Čapák, Ivo; Hulová, Markéta; Šebová, Natália; Lakomý, Radek; Jarkovský, Jiří; Doležel, Jan (Urologic oncology, 2022)
AIMS: Isolated retroperitoneal recurrence (IRR) in renal cancer patients after radical nephrectomy (RN) is a rare event and poses a therapeutic dilemma. We evaluated oncologic outcomes in surgically treated patients with IRR and established prognostic factors associated with survival. The benefit of metastasis-directed therapy (MDT) in those with clinical progression after extirpation of IRR was assessed. METHODS: This was a retrospective single-institutional study in which 60 renal cancer patients after previous RN underwent surgery for suspicion of IRR within the period of 2004-2019; in 55 of them, RCC recurrence was histologically confirmed. No patient had distant metastatic disease at the time of IRR diagnosis. In cases of clinical progression after IRR surgery, MDT (metastasectomy, stereotactic radiotherapy) was selectively used. Kaplan-Meier curves were used to estimate survival outcomes. Univariable and multivariable Cox proportional hazards regression analyses were used to evaluate associations between clinicopathological parameters and cancer-specific survival. RESULTS: Median age at IRR diagnosis was 64 years (range 23-81). IRR was diagnosed at a median of 42 months (IQR 19-99) after RN. Surgical complications of grade 3-5 after IRR extirpation were rare (7%). Median follow-up time was 50 months (IQR 19-80). Five-year recurrence-free survival and cancer-specific survival rates were 32% and 66%, respectively. Radiographic progression was observed in 34 (62%) patients at a median of 11 months after IRR surgery, out of which 22 patients (40%) underwent MDT. When compared with 12 patients without MDT, the MDT patients had a prolonged median time to systemic treatment of 58 (vs. 16 months), and median cancer-specific survival of 88 (vs. 46 months). Upon multivariable analysis, the interval from nephrectomy ≤12 months (HR 7.77), tumour grade 3-4 (HR 13.24) and female sex (HR 7.42) were determined to be independent prognostic factors of cancer-related mortality. CONCLUSION: Aggressive surgical therapy of IRR is feasible with relatively low morbidity. More than half of the patients experience long-term survival. The interval from nephrectomy to IRR less than 12 months, tumour grade 3-4 and female sex were negative prognostic predictors. In the case of progression, metastasis-directed therapy may prolong the interval to initiation of systemic treatment.
Keywords: dospělí; nádory ledvin; senioři nad 80 let; retrospektivní studie; Humans; Carcinoma, Renal Cell; lidé středního věku; lokální recidiva nádoru; Kidney Neoplasms; Middle Aged; Aged, 80 and over; Young Adult; Nephrectomy; karcinom z renálních buněk; mladý dospělý; nefrektomie; mužské pohlaví; Neoplasm Recurrence, Local; Adult; Retroperitoneal Neoplasms; ženské pohlaví; lidé; retroperitoneální nádory; Aged; senioři; Male; Retrospective Studies; Female